Improving MPPT system performance through improved Perturb and Observe algorithm in solar power plant system - Dwi Putra, Vandy; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2024)
This study evaluates the performance of Maximum Power Point Tracking (MPPT) algorithms using conventional and modified Perturb and Observe (P&O) methods in photovoltaic systems. Tests were conducted across irradiance levels of 200-600 W/m². Results demonstrate that the modified P&O method significantly reduces oscillations and improves convergence speed compared to the conventional approach. At 600 W/m² irradiance, the modified method achieves MPP in 325 ms with 9.85 W power output, while the conventional method requires 345 ms, producing 8.775 W. Increased irradiance correlates positively with power output and negatively with MPP tracking time. This research validates the effectiveness of the modified P&O method in enhancing efficiency and stability of MPPT systems in photovoltaic applications